The Jews and British Romanticism - Spector, S. author. aut Link
XIV, 334 p.
Keywords: Expanding the perspective initiated by British Romanticism and the Jews: History, Culture, Literature (0-312-29522-7), this volume explores more deeply the complexities inherent in the relationship between the British and Jewish cultures as initiated in the Romantic Period in England, though extending to the present in the Middle East.